Let f (x) = –5x + 3 and g(x) = 6x – 2, how do you find f • g and its domain?

1 Answer
Jul 25, 2016

(f*g)(x)=-2(15x^2-14x+3), x in RR.

Explanation:

Let D_f and D_g be the domains of the given funs. f and g, resp.

We can easily see that, D_f=D_g=RR

Now, by defn. the fun. f*g is defined by, (f*g)(x)=f(x)*g(x),

where, x in D_f nn D_g.

Since, D_f nnD_g=RR, we have, #(f*g) : RR rarr RR, where,

(f*g)(x)=f(x)*g(x)=(-5x+3)(6x-2)=-30x^2+10x+18x-6=-30x^2+28x-6.

Thus, (f*g)(x)=-2(15x^2-14x+3), x in RR.